Classical conditioning in patients with severe memory problems. Issue 1 (January 1989) - Daum, I; Channon, S; Canavan, A G
Abstract : Classical conditioning is one of the most fundamental forms of learning, and yet little is known regarding the effects of brain injury on conditioning processes in humans. Three patients with temporal lobe lesions and severe memory problems were therefore assessed in terms of eyeblink conditioning, extinction, discrimination and reversal learning, and in one patient electrodermal conditioning was also investigated. The acquisition of conditioned responses was seen to be intact, but the evidence regarding extinction was ambiguous. All of the patients were impaired in discrimination learning and also reversal learning.